Study the Effect of Cognitive Learning Strategies in the Achievement of the Students of Fifth Year Scientific Branch in Arabic Grammar - Zqair al-Maamouri, Mousa Kadhim (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims at identifying the Cognitive Learning Strategy in the achievement of the students of fifth year scientific branch in Arabic grammar, so in order to achieve this aim; the researcher used an experimental design of partial adjustment after the researcher has been choosing randomly Al-Thawra Preparatory School in Babylon city in order to apply the experimental in. The sample of this study made up of (64) students (32 students of the experimental group and 32 students of the control group). The researcher has divided the Cognitive Learning Strategy between the two groups of this study randomly, so the Cognitive Learning Strategy has applied on the experimental group, while the researcher has applied the traditional method on the control group. The researcher has equaled between the three groups of the study according to the following variables: age in months, the marks of Arabic grammar in the last semester, parents’ academic achievement, although there was no significantly differences at the level (0.05). The researcher has selected the topics which will be studied; he has used specific stylistic aims of the specific topics, after presenting these stylistic aims in initial form to some juries and specialists in Arabic Language Teaching Methods in order to verify its validity, finally, there was (30) stylistic aims that have formed. When the experimental of this study has applied, the students of the two groups of this study has been studied by the researcher himself for seven weeks, then the researcher has applied the summative assessment among the students of the two groups after preparing an achievement topic that made up of (30) items (multiple choice questions ‘MCQ’), which was characterized by stability and validity, which has applied on a sample survey that made up of (50) students in another school (Babylon Applied Secondary School), then the researcher has calculated the items difficulty coefficient and items discrimination and he has extracted reliability coefficient by using split-half method. Then the researcher has applied the summative assessment on the sample of this study. He has processed the data statistically by using one-way analysis of variance (ANOVA). When the researcher has gotten the final results, the results showed that the student of the experimental group were superior to the students of the control group in the summative assessment, the statistical significantly differences were at the level (0.05). Through the results, the researcher recommended that “it is necessary to use Cognitive Learning Strategy in teaching Arabic Grammar. In order to complete the present study, the researcher has suggested making other studies on different stages and in other different topics in Arabic grammar.